The effects of excessive disodium ethylene diamine tetraacetic acid (Na2EDTA) anticoagulant concentration toward hematology profile and morphology of erythrocytes in peripheral blood examination (Medical Journal of Indonesia, 2006)
The purpose of this study is to know whether there are differences between hematology profile and morphology of erythrocytes of blood specimens which are prepared with excessive Na2EDTA anticoagulant in different concentration. This study was conducted in Faculty of Medicine Gadjah Mada University. The criteria of subject were male, age from 18 until 22 years old and healthy, ascertained from history taking and vital sign examination. Blood samples from 33 subjects were taken using vein puncture. Two millimeters blood was divided into 4 Na2EDTA-containing tubes. Before that, one drop of blood without Na2EDTA anticoagulant was used for making control blood film right after vein puncture. Each tubes contained different concentration of anticoagulant. The first tube contained Na2EDTA in standard concentration 2 mg/dl; the remaining tubes contained consecutively, 4 mg/dl, 6 mg/dl, and 8 mg/dl. Those samples were immediately examined using SYSMEX SE-9500 automatic analyzer for measuring erythrocytes hematological profile and were stained with Wright staining for morphological examination. These procedures were done before 20 minutes of vein puncture. There were significant decrease of RBC count, HGB, HCT, and MCHC and also significant increase of MCV and RDW between different concentrations of excessive Na2EDTA anticoagulant. MCH did not have significant result. Morphological examination showed significant morphological changes in the form of echinocytes and appearance of ghost cells in the sample treated with excessive Na2EDTA anticoagulant concentration. In conclusion, there are differences in hematological profile and morphology of erythrocytes among blood specimen which are prepared with excessive Na2EDTA anticoagulant in different concentration, except for MCH. Excessive Na2EDTA anticoagulant concentration will affect the blood specimen for peripheral blood examination of erythrocytes by interfering morphology and some of hematological parameters. (Med J Indones 2006; 15:157-64) Keywords: Na2EDTA, erythrocytes, hematology parameters, echinocytes, ghost cells